Rarity constituent of forest phytocoenoses in Ukrainian Forest-Steppe - Bondaruk, M. A.; Tselishchev, O. G.; Bondaruk, G. V. (Forestry and Forest Melioration, 2019)
Introduction The article analyzes the inventory of rare constituent in Ukrainian forest flora along with its natural-zonal and administrative-regional spectra for establishment of systematic forest monitoring. As known, 199 species (or 32.6%) from 611 vascular plant species of national conservation status are growing in Ukrainian forests, almost half of which (49.2%) are growing in the forests of the Forest-Steppe forestry region. The aim of the study was to evaluate the condition of rare plant species and their spread in forest phytocoenoses in Ukrainian Forest-Steppe in order to organize a systematic forest monitoring. Materials and Methods We sampled 642 first-level monitoring plots located within all regions of the forest-steppe plain part of Ukraine and prepared a geobotanical description. The latter included tree, shrub and herbaceous plant species with the estimation of their abundance-coverage (%) by means of the combined scale by G. M. Vysotsky and D. V. Vorobyov. Rare plant species that are subject to special conservation within the territory of Ukraine and Europe were distinguished according to the lists of IUCN, Bern Convention, the European Red List, the Red Book of Ukraine and regional red lists, as well as endemic and relic species, and species on the border of their area. Furthermore, the category of rare species occurrence was determined. The development of their populations according to the degree of abundance-projective coverage was estimated at the rate of their distribution and the nature of development within the regional centers and Forest-Steppe region. Results Rarity constituent of forest phytodiversity in the Forest-Steppe forestry region is represented by 56 species with national (14 species) and regional (42 species) conservation status, which is 13.9% of the total number of flora species identified within the monitoring plots and 14.3% of 98 species of forest species within woodlands of the Forest-Steppe region with national conservation status. Most of the rare species (53 species) belong to the shrub-grass-moss layer, 2 species are shrubs and 1 species is a tree. The presence of rare species populations with national and regional conservation status within the investigated area (not only in natural forests, but also in planted ones) is a positive fact. However, most species, including all species with the national conservation status, occur very scarcely (1–4 localities) or scarcely (4–6 localities) with low abundance-coverage indicators (up to 5%). The species with the national conservation status are rare due to several reasons, namely the interrelated action of natural rarity, negative natural factors and anthropogenic impact. The species with the regional conservation status are of secondary rarity which is brought about by anthropogenic impact. Convallaria majalis L. and Pteridium aquilinum (L.) Kuhn populations are characterized by relatively high rates of occurrence, abundance-coverage and satisfactory restoration, which mean it is necessary to reconsider their conservation status as regionally rare species: Convallaria majalis for Poltava and Vinnytsia Regions, Pteridium aquilinum – for Poltava Region. Conclusions Regular monitoring (every 3–5 years) at the local, regional and subzonal levels in different ecotopes and habitats will allow researchers to evaluate the rarity level of one or another rare forest flora species populations, as well as to predict how their locality area will expand and get distributed in the region’s forests. Regular monitoring will also enable experts to anticipate the consequences of anthropogenic impacts, as well as to make decisions on a necessity to implement certain forms of conservation regime and to optimize the strategy for rare species conservation. 1 Table, 14 Refs.